For myself or for the group : a study of the effects of cognition- and affect-based trust and individualism-collectivism. - Ho, Sharon Ern Huey. (2008)
This project studies the effects of the interaction between affect- and cognition-based trust on cooperative behavior in a social dilemma. In addition, we provide insight into how individuals with different individualism-collectivism orientation react to the combinations of trust. We provide a discussion of these interesting findings and their practical implications.